Case of Pilgrimage Funds Management Board (Lembaga Urusan Tabung Haji) - Ahmad, Khaliq; Mohammed, Mustafa Omar; Abdul Razak, Dzuljastri (IIUM Press, 2012)
Lembaga Urusan Tabung Haji (LUTH) (Tabung Haji in Bahasa Malaysia) is a successful model of pilgrimage management for the Muslim world. It began operations in Malaysia in September 1963 with a vision of providing rapid and professional services to the pilgrims, achieved through managing deposits and investments efficiently. Tabung Haji also handles all Hajj operations and ensures pilgrims’ needs are well served. The organization has evolved efficiently by adopting participative internal management, contemporary marketing techniques and stateof-the art technology. It applies Shariah principles in managing the deposits and investments and in offering Hajj services